The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.2214/ajr.15.15182
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Cutaneous Melanoma by Use of Very- High-Frequency Ultrasound and Real-Time Elastography

Abstract: Our study showed that very-high-frequency ultrasound and real-time elastography can be useful examinations for comprehensive preoperative evaluation of cutaneous melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 32 publications
2
38
0
Order By: Relevance
“…Reduced elasticity correlates with tumour congestion and hypervascularization [6][7][8]. This case report emphasizes the importance of US in evaluating cutaneous tumours and its impact on therapeutic approach optimisation.…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…Reduced elasticity correlates with tumour congestion and hypervascularization [6][7][8]. This case report emphasizes the importance of US in evaluating cutaneous tumours and its impact on therapeutic approach optimisation.…”
Section: Introductionmentioning
confidence: 65%
“…In the case of benign tumours, colour Doppler usually shows a peripheral blood supply with a slow "wash out" time while performing contrast agent investigation [6]. Qualitative elastography based on a standard colour code, revealed an increased rigidity of both tumours, suggesting malignant lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies verifying elastography as a method to examine skin pathologies involved primarily cancer patients [23][24][25][26][27] and individuals with chronic systemic inflammation [28][29][30][31][32][33][34][35][36]. Most of these studies confirmed that elastography is an accurate method to identify and quantify proliferative and fibrotic processes taking place in the skin.…”
Section: Application Of Elastography In Dermatologymentioning
confidence: 86%
“…Diagnostic imaging plays little role in the initial diagnosis of melanoma, although high-resolution sonography is being studied to replace excision biopsies of cutaneous tumours (Botar-Jid et al, 2016). Imaging plays a major role in staging and follow-up of melanoma and in posttreatment assessment of metastatic melanoma.…”
Section: Radiologymentioning
confidence: 99%